CHECKLIST, RICHNESS OF COMMON NAMES AND CONSERVATION ISSUES OF MARINE FISHES LANDED IN COMMERCIAL FISHERIES OF ESPÍRITO SANTO STATE, BRAZILIAN CENTRAL COAST: Fishes landed in Espírito Santo, Brazil - Musiello Fernandes, Joelson; Andrades, Ryan Carlos de; Pimentel, Caio Ribeiro; Bolzan, Michelle Sequine; Schwingel , Andreia; Hostim-Silva, Maurício (Arquivos de Ciências do Mar, 2020)
The aim of this manuscript is to provide the first checklist of marine commercial fish species landed in Espírito Santo state (Brazilian central coast), with associated richness of common names and conservation status. The data collection took place under the Fisheries Monitoring Program, throughout the state of Espírito Santo. Altogether 22 fishing landing ports were monitored from May 2011 to August 2012. A total of 91 fish species from 39 families were identified. The richness of common names of fishery resources in Espírito Santo showed an average of two common names per species.